Opioid-induced short-term consciousness improvement in patients with disorders of consciousness - Ge, Qianqian; Wang, Yanjun; Zhuang, Yutong; Li, Qinghua; Han, Ruquan; Guo, Wenzhi; He, Jianghong (Frontiers in Neuroscience, 2023)
Introduction Effective treatment to facilitate recovery from prolonged disorders of consciousness is a complex topic for the medical community. In clinical practice, we have found that a subset of patients has a short-term improvement of consciousness after general anesthesia. Methods To determine the clinical factors responsible for the consciousness improvement, we enrolled 50 patients with disorders of consciousness who underwent surgery from October 2021 to June 2022. Their states of consciousness were evaluated before surgery, within 48 h after surgery, and 3 months after surgery. Clinical-related factors and intraoperative anesthetic drug doses were collected and compared between patients with and without consciousness improvement. Independent associations between selected factors and postoperative improvement were assessed using multivariate logistical regression analyses. Results Postoperative short-term consciousness improvement was found in 44% (22/50) of patients, with significantly increased scores of auditory and visual subscales. Patients with traumatic etiology, a preoperative diagnosis of minimally conscious state, and higher scores in the auditory, visual, and motor subscales were more likely to have postoperative improvement. This short-term increase in consciousness after surgery correlated with patients’ abilities to communicate in the long term. Furthermore, the amount of opioid analgesic used was significantly different between the improved and non-improved groups. Finally, analgesic dose, etiology, and preoperative diagnosis were independently associated with postoperative consciousness improvement. Discussion In conclusion, postoperative consciousness improvement is related to the residual consciousness of the patient and can be used to evaluate prognosis. Administration of opioids may be responsible for this short-term improvement in consciousness, providing a potential therapeutic approach for disorders of consciousness.